Chitosan as a Novel Edible Coating for Fresh Fruits - SHIEKH, Rayees Ahmad; MALIK, Maqsood Ahmad; AL-THABAITI, Shaeel Ahmed; SHIEKH, Muneer Ahmad (FOOD SCIENCE AND TECHNOLOGY RESEARCH, 2013)
The main benefits of edible active coatings are to maintain the quality and extend shelf-life of fresh fruits and prevent microbial spoilage. Chitosan have a wide range of potential application in different fields of chemical sciences, biological systems, food sciences, pharmaceutical and medical industries. Chitosan has been proven one of the best edible and biologically safe preservative coatings for different types of foods because of its film-forming properties, antimicrobial actions, lack of toxicity, biodegradability and biochemical properties. It has been proven that the chitosan can control numerous pre and postharvest disease of fresh fruits. Chitosan edible coatings extend the shelf life of the fruits and vegetables by minimizing the rate of respiration and reducing the water loss. Chitosan coating offers a defensive barrier against bacterial contamination and loss of moisture from the surface of food products, thus extending their shelf life. With limited increase in the concentration of chitosan coating, the beneficial effect of chitosan on postharvest life and quality of the food is enhanced. The present review delineates the preparation, properties and potential application of chitosan coatings for enhancing the postharvest life and quality of different types of fruits.